Maximizing Bulb Yield and Quality of Onion (Allium Cepa L.) Through Agronomic Management of Phosphorus Fertilizer and Transplanting Date Under Irrigation in Alaba, Ethiopia. - Anbes, Tilaye; Worku, Walelign; Beshir, Hussien Mohammed (Journal of Tropical Crop Science, 2022)
Bulb yield and quality of the onion is constrained by a number of factors, including inappropriate transplanting age and poor fertilizer management practices. Therefore, a field experiment was conducted to determine the best transplanting date on quality, combined with phosphorus level, on onion yield of onion. The study was conducted at Alaba, Ethiopia, during 2018/19 season. The treatments consisted of four phosphorus levels, i.e., 0, 20, 40 and 60 kg.ha-1, and three transplanting dates, i.e., 42, 49 and 56 days, from sowing. The experiment was laid out in randomized complete block design with four replications. The result showed that transplanting date and phosphorus rate significantly affected bulb dry weight and marketable bulb yield which includes medium and large sized bulbs. Among these parameters, marketable bulb yield was also significantly affected by the interaction of transplanting date and phosphorus rate. In this study, onion fertilized with P at 60 kg.ha-1 transplanted at 56 days had the highest marketable bulb yield. The economic analysis revealed that the highest net benefit with the lowest cost of production was obtained from the application of P at 40 kg.ha-1 and the transplanting at 56 days. The marginal rate of return for this treatment was economically feasible for producing onion bulb in the districts.